Atrophy of the lateral geniculate nucleus in human glaucoma detected by magnetic resonance imaging. Issue 1 (12th August 2008) - Gupta, N; Greenberg, G; de Tilly, L Noël; Gray, B; Polemidiotis, M; Yücel, Y H
Abstract : Aim: To determine in vivo whether the lateral geniculate nucleus (LGN) undergoes atrophy in patients with glaucoma and vision loss compared with normal subjects. Methods: Following institutional St Michael's Hospital Research Ethics Board approval, a prospective and masked neuroimaging study was conducted on glaucoma patients with visual-field defects affecting both eyes (n = 10) and age-matched controls (n = 8). Following informed consent, all subjects underwent 1.5-Tesla MRI. Coronal proton density magnetic resonance images of both LGNs were obtained, and LGN height measurements were measured by consensus by three neuroradiologists masked to the diagnosis. Glaucoma and control groups were compared using the t test. Results: Both LGNs were identified and visualised by 1.5-Tesla MRI for every subject. Compared with controls, the mean LGN heights in glaucoma were decreased in right (4.09 (0.89) mm vs 4.74 (0.54) mm, p>0.05) and left LGNs (3.98 (0.57) mm vs 4.83 (0.95) mm; p = 0.033). The combined right and left LGN height in glaucoma was significantly decreased compared with controls (8.07 (1.06) mm vs 9.56 (0.86) mm; p = 0.005). Conclusion: In vivo MRI evidence of LGN degeneration in human glaucoma is consistent with ex vivo primate and human neuropathological studies. LGN atrophy may be a relevant biomarker of visual system injury and/or progression in some glaucoma patients.